Pengaruh Motivasi Kerja Dan Kepuasan Kerja Terhadap Organizational Citizenship Behavior (OCB) Karyawan Bakti Timah Medika - Muchtadin Muchtadin; Zelvy Emmelya Sundari (Universitas Kristen Indonesia Toraja, 2022)
Organizational Citizenship Behavior is an important aspect for employees in the health sector. This study aims to determine how much work motivation and job satisfaction have an impact on employee OCB. Multiple regression analysis was used as a method of data analysis and descriptive analysis to find out the general description of the respondents. The findings in this study conclude that work motivation and job satisfaction both simultaneously and partially have a positive impact on OCB. The company is expected to pay attention to the motivation and job satisfaction of its employees so that they work more at work and work beyond the applicable formal rewards.